Smart agronomic practices for growing crops in salt-affected soil - Yadav, Arvind; Kumar, Avaneesh; Kumar, Sandeep (Indian Farming, 2024)
India, which occupies 2.4% of the world's land area, has to feed 17% of the world's population and 15% of its livestock. With a projected population of 1.43 billion in 2030 and 1.8 billion in 2050, demand for food is increasing. However, 146.8 million hectares of land is degraded, resulting in an annual soil loss of 5.3 billion tonnes, threatening food security. Saline soils in states like Gujarat, Uttar Pradesh, Maharashtra, West Bengal and Rajasthan are deteriorating agricultural productivity. Solutions include managing salt-polluted soils with gypsum, phosphogypsum, sulfonated press mud and biodrainage, besides salt-tolerant crops and biosaline agriculture. Promoting agroforestry with salt-tolerant trees and climate-smart practices is critical. A holistic approach that integrates technology, agriculture and environmental strategies is critical to food security.